Genetic Polymorphism of the DCT gene in local ducks raised in Iraq - Majeed Shareef, Hussein; Sajida. A. Al-Shaheen, Sajida. A. Al-Shaheen (University of Thi-Qar Journal of agricultural research, 2025)
The study was conducted in the field of waterfowls birds breeding / College of Agriculture / University of Basrah during the period from 5/12/2023 to 1/30/2024, to detect the genetic polymorphism of the (DCT) gene. In this study (270 chicks from three genetic groups of local ducks were used according to the feather colours (white, gray) and mallard ducks with (90) chicks for each group. (25) blood samples were collected from each group at the age of (6) weeks. DCT gene amplification and DNA sequencing revealed four base-change sites (70T>C), (148C>T), (234G>A), and (370A>G) and a group of alleles associated with feather colour. The genotypes showed an equilibrium of different mutation sites, the genetic mutation (70T>C) was equilibrium in all feather colour groups of ducks, while the other genetic mutation (148C>T) is for ducks with gray and mallards, and the two genetic mutations (234G>A) for white and (370A>G) are in ducks with white and gray feathers. Shannon’s index values ​​increased for all mutation sites in local ducks. The frequencies of observed heterozygous genotypes were higher than the frequencies of observed homozygous genotypes, and negative values ​​for the stability index were recorded for all mutation sites.